Analisis Sistem Logistik Rantai Pasok Substitusi Bahan Baku PLTU Batu Bara Menggunakan Soft System Methodology (SSM) - Wan Habibi Rahman Barus; Iphov Kumala Sriwana; Nadiya Maharani; Muhammad Alif Ihsan (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
The use of coal as the primary raw material for Steam Power Plants (PLTU) poses serious challenges related to sustainability, particularly due to high emissions, pollution risks, and supply chain dependence on non-renewable energy sources. Partial coal substitution with biomass is considered an effective strategy to reduce environmental impacts while supporting new and renewable energy targets. This study aims to analyze the potential of palm oil solid waste, wood pellets, and charcoal briquettes as coal substitutes using the Soft System Methodology (SSM) approach. The study follows seven SSM stages, starting from problem identification, compiling a problem description, formulating a root definition, CATWOE analysis, building a conceptual model, a debating process, and recommending corrective actions. The analysis results indicate that biomass substitution is feasible if supported by an integrated logistics system, the availability of biomass supplies, and compliance with the technical specifications for PLTU combustion. Biomass from palm oil waste, wood waste, and agricultural residues has a fairly stable energy value and can be obtained through a more environmentally friendly supply chain. Overall, this study confirms that the SSM approach is effective in understanding the complexity of coal-fired power plant problems and formulating renewable energy-based solutions through strengthening the biomass logistics system.Keywords - Biomass, PLTU, Renewable Energy, Soft Systems Methodology, Supply Chain Logistics.